The idea of cultural heritage - Gillman, Derek (New York : Cambridge University Press, 2010)
'The idea of cultural heritage has become widespread in many countries, justifying government regulation and providing the background to disputes over valuable works of art and architecture. In this book, Derek Gillman uses several well-known cases from Asia, Europe, and the United States to review the competing claims that works of art belong either to a particular people and place, or, from a cosmopolitan perspective, to all of humankind. Noting the importance of cultural roles and narratives in shaping heritage, he looks at the ways in which the idea of heritage has been constructed. He focuses first on Britain and the writings of Edmund Burke and then on China and its medieval debate about the nature of'our culture.' Drawing on a range of sources, including the work of Ronald Dworkin, Will Kymlicka, and Joseph Raz, Gillman relates debates about heritage to those in contemporary political philosophy and offers a liberal approach to moral claims and government regulation'--Provided by publisher.
pt. 1. Claims about heritage -- Heritage and national treasures --'Two ways of thinking' -- pt. 2. Heritage and narrative -- Constructing British heritage --'This culture of ours' -- pt. 3. Regulation and rights -- Regulation and private rights -- Liberalism and valuable practices.
Includes bibliographical references and index.
Keywords: Antiquities -- Collection and preservation; Historic preservation; Historic preservation -- Political aspects; Cultural property -- Protection; Cultural property -- Protection (International law)